Effetti biologici da esposizione occupazionale a campi magnetostatici utilizzati in imaging a risonanza magnetica nucleare: una rassegna / Health effects of occupational exposure to static magnetic fields used in magnetic resonance imaging: a review - Franco, G.; Perduri, R.; Murolo, et al., A. (La Medicina del Lavoro, 2008)
I dispositivi per l’imaging a risonanza magnetica nucleare rappresentano una fonte di esposizione a campi magnetostatici (CMS) per i pazienti e per diverse categorie di lavoratori (tecnici sanitari di radiologia medica, radiologi, chirurghi, anestesisti, manutentori). Tale problema è reso attuale dal prossimo recepimento, che dovrebbe avvenire entro il 30 aprile 2008, nella legislazione italiana della Direttiva 2004/40/CE del 29 aprile 2004 relativa ai rischi associati agli effetti a breve termine derivanti dai campi elettromagnetici. Scopo dello studio è quello di revisionare criticamente la letteratura sugli effetti biologici per fornire un contributo relativamente agli adempimenti normativi previsti a proposito in tema di informazione e formazione e controllo dello stato di salute del personale esposto. Per identificare gli studi comparsi successivamente alla pubblicazione dedicata ai CMS dall’Organizzazione Mondiale della Sanità nella serie Environmental Health Criteria, è stata condotta una ricerca sulla base di dati Medline. Sono stati utilizzati i seguenti termini MeSH: (i) Magnetic Resonance Imaging, (ii) Electromagnetic Fields, (iii) Electromagnetic Fields/adverse effects, (iv) Occupational Health tra di loro variamente associati in modo da costruire specifiche stringhe di ricerca, per identificare gli studi appropriati. In base a criteri predefiniti sono stati selezionati 28 studi. Gli studi in vitro dimostrano che gli effetti biologici, espressione di diverse modalità e intensità di esposizione a CMS, sono causati da meccanismi diversi. Tuttavia non è possibile affermare che effetti specifici associati ai CMS esistano così come non è possibile sostenere la loro assenza. Gli studi sperimentali effettuati su volontari sani esposti a CMS di intensità variabile da 1 a 8 T hanno dimostrato la presenza di (i) vertigini e nausea dose-correlate, con sensazione di sapore metallico, (ii) aumento della pressione arteriosa sistolica all’interno della variabilità fisiologica, (iii) occasionali episodi di tachicardia sinusale reversibili, (iv) riduzione della memoria a breve termine, (v) alterazione della coordinazione occhio-mano. Gli studi epidemiologici, che hanno considerato lavoratori esposti a CMS nel corso di varie attività, hanno messo in evidenza risultati contraddittori dovuti a un’insoddisfacente misura dell’esposizione, alla presenza di fattori confondenti, alla loro ridotta dimensione. Alla luce dei risultati si ritiene che gli adempimenti relativi alla necessità di attuare le misure di tutela degli esposti a CMS potranno presentare non poche difficoltà in particolare per quanto riguarda le disposizioni dell’art. 6 (informazione-formazione) e dell’art. 8 (sorveglianza sanitaria) della direttiva. Questi adempimenti potranno infatti risentire delle incertezze relative alla mancanza di prove scientifiche, che da un lato richiederanno equilibrio e abilità nel comunicare i dubbi esistenti e dall’altro si rifletteranno sull’attuazione di un programma di controllo che includa accertamenti preventivi e periodici mirati alla prevenzione degli effetti a breve termine.Health effects of occupational exposure to static magnetic fields used in magnetic resonance imaging: a reviewIntroduction: Magnetic resonance imaging is an established diagnostic tool involving exposure to static magnetic fields (SMF) of patients and health personnel (radiology technicians, radiologists, anaesthetists, surgeons, maintenance staff ). Occupational exposure to SMF will be governed by the rules of European Union Directive 2004/40/EC covering health and safety requirements regarding the exposure of workers to risks from electromagnetic radiations, which must be incorporated into national law by each member state by 30 April 2008. It applies to all employment sectors and addresses short-term adverse health effects on workers, but excludes possible long-term effects. This study aims to critically review the recent literature on the topic so as to propose guidelines on the need to provide information and training of workers and appropriate health surveillance. Materials and methods: To identify the studies published after the review by the World Health Organization (WHO) in the series Environmental Health Criteria, a search was carried out on Medline. The strategy defined for searching studies was based on the following MeSH terms, which comprehensively addressed the problem: (i) Magnetic Resonance Imaging, (ii) Electromagnetic Fields, (iii) Electromagnetic Fields/adverse effects, (iv) Occupational Health. These terms were used to create appropriate search links to identify the studies according to the following criteria: (i) English language, (ii) inclusion of review, case-control and cohort study, controlled trials, (iii) abstract availability (iv) human effects, mechanism of action, pathophysiology or in vitro studies, (v) studies published after 1 January 2004 not considered in the WHO review. Twenty-eight studies were available as full-text. Results: Although studies carried out at cellular level are valuable in investigating mechanisms of interaction, they did not show any specific effect as a consequence of exposure to SMF. Experimental studies carried out on volunteers showed that short-term exposure to SMF induces a variety of acute effects: (i) vertigo, nausea and a metallic taste in the mouth occur during body or head movement with SMF in T range and may result in a possible negative influence on the performance of workers during critical procedures, (ii) changes in blood pressure and heart rate within the range of physiological variability occur for exposures to SMF up to 8 T, (iii) induction of ectopic heart beats and increased likelihood of reversible arrhythmia (possibly leading to ventricular fibrillation) may occur in susceptible workers) (iv) a decrease of working memory and eye-hand coordination are dose-dependent for exposures to 1.5-3 T SMF and may affect  the performance of workers executing intricate procedures. The limitations of the available studies, however, do not allow any firm conclusions to be drawn about the effects of SMF on the described endpoints. Conclusion: According to Directive 2004/40/EC, the employer must ensure that workers exposed to risks from electromagnetic fields receive all necessary information about the potential risks and that appropriate health surveillance is carried out to prevent any adverse health effects. According to the reported data it will not be easy to proved information and training and the appropriate health surveillance for the exposed workers. In fact, information and training activities might be influenced by the uncertainties resulting from the available evidence, since ability will be needed to find a balance between few certainties and several doubts, while the same uncertainties might reflect on the preventive and periodical examinations aiming at preventing short-term adverse health effects.